ANALYSIS OF EARNING MANAGEMENT AND CASH HOLDING TO DETECT WINDOW DRESSING BASED ON SHARIA PRINCIPLES: (Study of Companies Listed on the Jakarta Islamic Index (JII) for the 2021-2023 Period) - Asfiah, Farida; Ekawati, Evi; Susanto, Is (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to prove empirically about the analysis of earning management and cash holding to detect window dressing practices in Jakarta Islamic Index companies. The measurement of the independent variables is measured from each variable indicator. Quantitative research using secondary data, namely the annual financial statements of companies listed on the Jakarta Islamic Index (JII) for the 2021-2023 period with a causal associative approach. The results showed that the earning management variable had no effect on the window dressing variable. The cash holding variable has a significant negative effect on the window dressing variable. The findings of this study have major implications for users of financial statements that there is a relationship between earning management variables and cash holding variables on window dressing practices in an entity. This study provides evidence that companies listed on the Jakarta Islamic Index have considered social, moral, and ethical values of financial management in fulfilling sharia principles, especially companies listed on the Jakarta Islamic Index for the 2021-2023 period.